Becoming a reflective mathematics teacher : a guide for observations and self-assessment - Artzt, Alice F.; Armour-Thomas, Eleanor (Mahwah, NJ : Lawrence Erlbaum Associates, 2002)
Describes observation instruments and reflective activities that may be used by preservice teachers when observing the classroom work of other teachers, and includes case studies, as well as guidelines and instruments for supervisors.
Includes bibliographical references (p. 223-230) and indexes.
Choice.
Professional
Keywords: Mathematics teachers -- Psychology; Mathematics -- Study and teaching -- Evaluation; Mathematics -- Study and teaching -- Evaluation; Teachers -- Psychology